2018
DOI: 10.1177/1461444818810026
|View full text |Cite
|
Sign up to set email alerts
|

‘We always torment different people, so by definition, we are no bullies’: The problem of definitions in cyberbullying research

Abstract: In this article, we investigate the power of prevailing definitions within the research field of cyberbullying. We address how these definitions, mostly deriving from developmental psychology, have had a problematic influence on the way researchers, policymakers, practitioners working with interventions, and children and young people themselves approach the challenge of understanding and preventing cyberbullying and its consequences. We analyse how the definition of cyberbullying stemming from developmental ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…There currently exists considerable scholarly debate about the definitions of cyberbullying (Alipan et (Kofoed & Staksrud, 2019). One respondent in this study suggested that lateral violence in Indigenous communities on social media was indeed a negative aspect of social media but claimed they were "not sure if this is included as cyber bullying".…”
Section: Defining 'Cyberbullying'mentioning
confidence: 90%
“…There currently exists considerable scholarly debate about the definitions of cyberbullying (Alipan et (Kofoed & Staksrud, 2019). One respondent in this study suggested that lateral violence in Indigenous communities on social media was indeed a negative aspect of social media but claimed they were "not sure if this is included as cyber bullying".…”
Section: Defining 'Cyberbullying'mentioning
confidence: 90%
“…For example, there are no clear parameters for frequency (i.e., how often the behavior must be repeated) and duration (i.e., length of time within which the behavior must be repeated), nor any clear criteria regarding how severe the behavior needs to be in order to be considered as bullying on its first occurrence. In addition, the current conceptualization of repetition excludes perpetrators who consistently act aggressively towards different targets (Kofoed & Staksrud, 2019). Other ambiguities arise when applying the definitional principle to cyberbullying.…”
Section: Ambiguous Situations Involving Repetitionmentioning
confidence: 98%
“…Over the last 10 years, a body of research has expressed concerns around "the power of prevailing definitions" of cyberbullying in research (Kofoed & Staksrud, 2019); a concern that popular definitions have a problematic influence on how researchers, policymakers, and young people themselves approach the issue. Definitions, as Canty et al (2016) remind us, "are made not born" (p. 48); they have social, cultural, and academic histories that are often obscured through repeated use.…”
Section: The Standardization Of Definitionsmentioning
confidence: 99%
“…(p. 48) Staksrud (2019, p. 1007) heed Canty et al's (2016) warning and document the strange side effects of "definitional overlearning" in cyberbullying research, which can occur through anti-bullying efforts to educate children about bullying by providing them with existing models and definitions of bullying. This has produced "some puzzling side effects" (Kofoed & Staksrud, 2019, p. 1011, they observe, such as when students are surveyed and respond by telling researchers their definition is "wrong" because it doesn't match what they've already learnt elsewhere; or when students explain that they aren't "cyberbullying" because they only did it a single timemeaning it doesn't fit the official criteria. Their work demonstrates the ontological and social power definitions can have beyond academic circles, where children are taught the supposedly "right" definition of what constitutes cyberbullying.…”
Section: The Standardization Of Definitionsmentioning
confidence: 99%
See 1 more Smart Citation